Crutched Pharaoh, Seated Hunter: An Analysis of Artistic Portrayals of Tutankhamun’s Disabilities - Smith-Sangster, Emily.
Academic and popular sources alike regularly refer to Tutankhamun as “disabled” at the time of his death, citing artistic representations from the items in his tomb to back up such claims. This group of objects has been said to depict the young king seated while hunting and using a staff as a walking aid seemingly highlighting the presence of a leg-based disability. This narrative of the image depicting the truth of Tutankhamun’s physical condition has publicly become accepted as fact with images of the seated king even being used in the advertising for the touring exhibit “Tutankhamun: Treasures of the Golden Pharaoh” to suggest Tutankhamun’s “fragile constitution.” A comparison of these depictions to historical representations of kings hunting and using staffs of authority, however, suggests that these depictions of Tutankhamun were part of a traditional iconography utilized by Tutankhamun’s artists, not to highlight his disability, but instead to situate his image within the artwork of kings of the Old, Middle, and New Kingdoms. This study, thus, works to dispel the pervasive myth of the existence of artistic representations of a disabled Tutankhamun, while providing a basis for understanding the true nature of the representation of disability in Egyptian art. Furthermore, this work urges Egyptologists to avoid relying on physical remains to “decipher” mortuary artwork. Such a change in method can only lead to a better understanding of the purpose of the depicted body within the mortuary context and its role as separate but complementary to the physical body in New Kingdom thought.